2022
DOI: 10.21873/invivo.12994
|View full text |Cite
|
Sign up to set email alerts
|

Oral-recombinant Methioninase Lowers the Effective Dose and Eliminates Toxicity of Cisplatinum for Primary Osteosarcoma of the Mammary Gland in a Patient-derived Orthotopic Xenograft Mouse Model

Abstract: Background/Aim: Primary osteosarcoma of the mammary gland is a very rare disease, accounting for under 1% of all mammary gland malignancies. There is no established first-line treatment, and prognosis is poor compared to conventional breast cancer. We previously demonstrated the efficacy of cisplatinum and eribulin in a patient-derived orthotopic xenograft (PDOX) mouse model of primary breast osteosarcoma. However, these drugs show significant clinical toxicity. All cancers are addicted to methionine (Hoffman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The results of the present study suggest that rMETase, when combined with regorafenib, can reduce the effective dose of regorafenib and thereby also reduce its toxicity. Previously, we showed in an orthotopic mouse model of osteosarcoma that combining rMETase with cisplatinum reduced its effective dose by 50% (18). A similar effect is predicted for the combination of regorafenib and rMETase in future in vivo experiments.…”
Section: Discussionsupporting
confidence: 69%
“…The results of the present study suggest that rMETase, when combined with regorafenib, can reduce the effective dose of regorafenib and thereby also reduce its toxicity. Previously, we showed in an orthotopic mouse model of osteosarcoma that combining rMETase with cisplatinum reduced its effective dose by 50% (18). A similar effect is predicted for the combination of regorafenib and rMETase in future in vivo experiments.…”
Section: Discussionsupporting
confidence: 69%
“…Hoshiya et al originally demonstrated the synergistic efficacy of cisplatinum and methionine restriction in vitro and on a xenograft mouse model utilizing the human breast cancer cell line MX-1 (34). In addition, cisplatinum combined with rMETase showed efficacy for colon cancer cell lines (Colo205, SW620, HCT15, and HT29) xenograft mouse models (35), and osteosarcoma PDOX and orthotopic xenograft mouse models (36)(37)(38), and a bladder-cancer orthotopic mouse model (39).…”
Section: Platinum-based Chemotherapy Synergy With Methionine Restrictionmentioning
confidence: 99%
“…All mice were kept under standard conditions of 12 h light/dark cycles and were maintained and bred in a barrier facility with a high efficacy particulate air (HEPA)-filtered rack. An Institutional Animal Care and Use Committee (IACUC) protocol was approved, in accordance with the National Institutes of Health (NIH) Guide for the Care and Use of Animals, under Assurance Number A3873-1, as previously described in studies of mouse models of osteosarcoma (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Precise and Facile Endotracheal Lung-tumor-implantation Mous...mentioning
confidence: 99%